Effect of phosphorus management practices on growth, production and economics of wheat (Triticum aestivum) in an acid Alfisol - RANJHA, REWANGINI; SINGH, DHANBIR; SHARMA, SANJAY K; BAHMAN, MANSI; SAKSHI (The Indian Journal of Agricultural Sciences, 2025)
The study was carried out during winter (rabi) season of 2021–22 and 2022–23 at Chaudhary Sarwan Kumar Himachal Pradesh Krishi Vishvavidyalaya, Palampur, Himachal Pradesh to explore and understand the impact of different phosphorus management practices on wheat yield and quality in acid Alfisol of Himachal Pradesh. The experiment was laid out in a randomised block design (RBD) with nine treatments (T1, Control; T2,100% NPK; T3, 100% NPK + lime; T4, 100% NPK + 10 t/ha FYM; T5, 0.5 t/ha Ghan jeevamrit + Jeevamrit sprays at 21 days interval; T6, 100% NK + 3 t/ha PROM; T7, 100% NK + 75% P + 0.75 t/ha PROM; T8, 100% NK + 50% P + 1.5 t/ha PROM and T9, 100% NK + 25% P + 2.25 t/ha PROM) replicated thrice. The wheat variety selected for the study was HPW 368 variety. Crop growth parameters, such as plant height, tiller count, root volume, and root mass density were assessed along with yield attributes like productive tillers, grains/spike, and 1000 grain weight. The results indicated that the application of 1.5 t/ha PROM combined with 100% NK and 50% P through single super phosphate (T8) resulted in the highest plant growth, root development, grain yield (4.25 t/ha) and straw yield (6.45 t/ha). This treatment also produced the highest net returns (62,017 ₹/ha). Whereas, the highest B:C ratio was recorded under T2 treatment i.e. 100% NPK (1.83) followed by T8 (1.72), demonstrating superior economic viability. Thus, application of 100% NK + 50% P + 1.5 t/ha PROM to wheat crop was found best for realising higher growth, production and profitability under phosphorus-limited acid Alfisol conditions.